Sub-Acute Oral Toxicity of a Novel Derivative of Agomelatine in Rats in a Sex-Dependent Manner - Yang, Qiushi; Zhou, Xuelin; Li, Jingyi; Ma, Yi; Lu, Li; Xiong, Jie; Xu, Pingxiang; Li, Yuhang; Chen, Yi; Gu, Wei; Xue, Ming; Jin, Zengliang; et al. (Frontiers in Pharmacology, 2019)
Agomelatine (AGO) is a new type of antidepressant with demonstrated antidepressant effects and unique modulating circadian rhythms action. However, AGO has hepatotoxicity, which limits its clinical application. In order to develop new drugs with less liver injury than AGO, a series of derivatives were synthesized, compound GW117 was screened from derivatives due to its high receptor affinity. This study will investigate its sub-acute oral toxicity profile in rats in a sex-dependent manner. GW117 and AGO was administrated by gavage (200, 400, or 800 mg/kg/day) for 28 days. Hematological, biochemical tests, organ weights, histopathological examinations were carried out, the results showed that AGO and GW117 had adverse effects on platelet, liver and kidney, and had sex-differences in some indicators. Hematological tests showed that AGO and GW117 reduced platelet count in male animals, but had no effects in females. AGO increased plasma alanine aminotransferase (ALT) and total bilirubin in male animals, and GW117 had no effects on these two indicators. For females, AGO moderately elevated ALT, alkaline phosphatase (ALP), and total bilirubin, while GW117 only elevated ALP slightly. Two drugs could increase liver weight and coefficient, and cause liver pathological injury, including hepatic sinusoidal dilatation, hepatocyte fatty deposition, dotted cell necrosis in two genders. AGO caused mild to moderate hepatocyte and hepatobiliary injury in both genders, while only mild hepatobiliary injury was caused by GW117 in females. Renal function tests showed that both drugs can increase blood urea nitrogen levels in males, while AGO, but not GW117, can slightly increase blood creatinine and urea nitrogen in females. The kidney weight and coefficient can be significantly increased by two drugs in males, and by AGO medium, GW117 high and low doses in females. The kidney pathological damage was mainly characterized by tubule dilatation, thinning of renal cortex. Kidney damage caused by GW117 was less than that of AGO, and there was no sex-difference. In summary, GW117 could cause mild liver and kidney damage in two genders, mild platelets reduction in males, and the degree of damage is less severe than AGO, so as an excellent derivative, GW117 deserves further development as an antidepressant.